Knowledge, attitude and practice of neutering among dog owners in malaysia - Gayatri Sabrina A/P Rahu (2023)
An abstract of the research paper was presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement for the course DVT 55204 – Research Project. Neutering is a general term that refers to a surgical procedure involving the removal of the reproductive organs in both male and female dogs. There are several factors that contribute to the challenges associated with neutering in dogs, particularly, high cost of neuter surgery, dogs that are kept for breeding purpose, surgery risk and complication in certain dog breeds, not suitable age and condition of dogs and owners’ perception towards animal rights and welfare. However, there is still a lack of understanding and awareness regarding benefits of neutering to eliminate certain reproductive diseases and to control unwanted pregnancies in dogs. This cross-sectional study was carried out to assess the current knowledge, attitude and practice (KAP) regarding neutering of dogs among dog owners in Malaysia using a self-administered questionnaire via Google Form. The study findings showed that dog owners have good knowledge (n = 55, 43.3%), good attitude (n = 59, 46.4%) and moderate practice (n = 59, 46.4%) towards neutering in dogs. This study will benefit the public since the Department of Veterinary Services Malaysia (DVS) and Society for the Prevention of Cruelty to Animals (SPCA) are responsible in taking necessary measures, such as organizing neutering campaigns in order to raise community awareness in controlling stray population. In conclusion, gender, age, area of residential, level of income and education level were the significant factors that influenced dog owners’ knowledge, attitude and practice towards neutering in dogs.